قرآن مجید کی معاشرتی اصلاحات کی تفہیم و تشریح میں سید ابوالاعلیٰ مودودی اور مولانا وحید الدین خان کے افکار کا تقابلی مطالعہ: A comparative study of the Thoughts of Syed Abul Ala Maududi and Molana Wahiduddin Khan in the understanding and interpretation of the Social Terms of the Holy Quran - Ataullah; Dr, Sana ullah Hussain (jihat-ul-islam, 2023)
Syed Maududi and Wahiduddin Khan wanted reform in the light of traditional thought. Both of these figures were convinced of the conditional use of Western thought and believed in the principles of the Qur'an and Sunnah as the basis for social reforms, however, there is a difference between them in some matters. Syed Maududi declares democratic politics as essential for the reform of the society. With him, the strategies for social reform can be changed. Therefore, Jamaat-e-Islami emerged as a preaching and reform movement and later became a part of the democratic system. And then it became a charity organization by changing its management. They also have military menhaj for reform. Their call is to establish the name of God's system on God's land instead of the concern of individuals. Allama Wahiduddin Khan's thought is scientific and experimental. He always tries to match the verses of the Holy Quran with the experiences of contemporary science. The style of remembrance is prominent in his writings. There are modernist tendencies and inclinations in the thoughts and ideas, they are the bearers of the individual ideology compared to the collective ideology and they are convinced of independent ijtihad in reforming the society. Some of Maulana Wahiduddin Khan's beliefs and ideas are quite different from those of the Jamahur Ahl al-Sunnah.